What is the factored form of the expression? 18x^2-9x-9

18x^2 - 9x - 9 = 9(2x^2 - x - 1) = 9(2x + 1)(x - 1)

g
googletag.cmd.push(function() { googletag.display('div-gpt-ad-1564665647093-0'); });

Question

Asked 11/10/2014 5:24:04 PM

Updated 11/10/2014 8:17:26 PM

2 Answers/Comments

Rating

8

18x^2 - 9x - 9

= 9(2x^2 - x - 1)

= 9(2x + 1)(x - 1)

= 9(2x^2 - x - 1)

= 9(2x + 1)(x - 1)

Added 11/10/2014 8:17:11 PM

This answer has been confirmed as correct and helpful.

34,466,363

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 818 [Total 6691] Ratings 19 Comments 628 Invitations 0 Online

There are no comments.